Analisis Pengelolaan Rasio Keuangan Berdasarkan Implementasi UU Nomor 1 Tahun 2022 pada Pemerintah Kabupaten Sukabumi - Ahmad Zulkifly Salman; Vicky Dzaky Cahaya Putra (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze financial ratio management based on the implementation of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments (HKPD Law) in the Sukabumi Regency Government. The implementation of the HKPD Law has brought significant changes to the structure of the Regional Revenue and Expenditure Budget (APBD), particularly in the regional transfer mechanism such as the General Allocation Fund (DAU), which is divided into block grants and specific grants. These changes have implications for regional financial management patterns and fiscal performance as reflected in financial ratios. This research employs a descriptive method with a qualitative approach. The data consist of primary data obtained through interviews with officials of the Regional Financial and Asset Management Agency (BPKAD) of Sukabumi Regency and secondary data in the form of APBD realization reports for the fiscal years 2021–2024. The analysis uses financial ratio indicators, including the independence ratio, effectiveness ratio, efficiency ratio, expenditure harmony ratio, and Regional Original Revenue (PAD) growth ratio. The results indicate that the implementation of the HKPD Law affects the structure of regional revenues and expenditures and requires adjustments in fiscal management. Changes in the DAU mechanism and strengthened regulation of regional taxation present both challenges and opportunities to enhance fiscal capacity and regional independence. Therefore, adaptive financial management strategies are needed to ensure that the objectives of fiscal decentralization are optimally achieved.